Effect of balance training on footwork performance in badminton: An interventional study - Malwanage, K. T.; Senadheera, V. V.; Dassanayake, T. L. (PLOS ONE, 2022)
Badminton is a racket sport that requires a wide variety of proficient postural changes and moves including jumps, lunges, quick changes in direction, and rapid arm movements. Efficient movement in badminton court entails reaching the shuttlecock in as few steps as possible while maintaining good balance. Balance training is an unexplored component in badminton training protocol, though balance is important in injury prevention and performance enhancement. We aimed to investigate the effectiveness of balance training on sport-specific footwork performance of school-level competitive badminton players. We conducted a controlled trial involving 20 male badminton players (age 12.85±0.67 years). Participants were stratified according to their level of performance in the game, and payers from each stratum were randomly assigned to control and intervention groups. The control group (n = 8) engaged in 2 hours of ordinary badminton training, whereas the intervention group (n = 12) underwent 30 minutes of balance training followed by 1 hour and 30 minutes of ordinary badminton training, 2 days per week for 8 weeks. We tested the participants at baseline and after 8 weeks for static balance (Unipedal Stance Test), dynamic balance (Star Excursion Balance Test) and sport-specific footwork performance (shuttle run time and push-off times during stroke-play). On pre- vs. post-intervention comparisons, both groups improved in static balance (eyes opened) (p<0.05), but only the intervention group improved in dynamic balance (p = 0.036) and shuttle-run time (p = 0.020). The intervention group also improved push-off times for front forehand (p = 0.045), side forehand (p = 0.029) and rear around-the-head shots (p = 0.041). These improvements in push-off times varied between 19-36% of the baseline. None of the footwork performance measures significantly improved in the control group. Our findings indicate that incorporating a 30-minute balance training program into a regular training schedule improves dynamic balance, and on-court sport-specific footwork performance in adolescent competitive badminton players, after 8 weeks of training.